OKR tool applied to agribusiness: A case study - Carmo, Vitor Antônio Silva; Pinheiro, Renes Rossi; Alvarenga, Samia Mercado; Potrich, Ani Caroline Grigion (Seven Editora, 2024)
This work focuses on the application of the OKR (Objectives and Key Results) tool in the context of agribusiness, an area traditionally governed by more conventional management methodologies. The objective of this work is to identify the contribution of the OKR tool to the strategic results of the company. To achieve this goal, a case study was carried out in a specific company in the sector. As a data collection procedure, a documentary review was carried out, collecting quantitative and qualitative information in the company's internal reports. The result suggests that, maintaining the pace and planning established for the year 2023, the goal of earning 1 million tons - which is the main metric to evaluate the company's success - should be achieved. This projection is supported by the results already obtained: until August, the company earned 257,538 tons, a number that is in line with the monthly forecasts established for the entire year, since in agribusiness we have a seasonality for the purchase of inputs, centralizing sales in the months of September and October where the harvests of some crops occur. In this way, OKRs emerge as a valuable tool for the agribusiness sector. The study suggests that in order to maximize the benefits of OKR in agribusiness, it is essential to consider the specifics of the sector when establishing objectives and key results. DOI:https://doi.org/10.56238/sevened2024.007-099